Acne Management in Transgender Men and Boys. Issue 6 (November 2021) - Somers, Kathryn; Greenberg, Katherine
ABSTRACT: Transgender men often seek hormonal therapy with testosterone and are thus prone to develop acne. Dermatology practitioners should be knowledgeable in the treatment of acne in transgender men. Isotretinoin and the iPledge system have particular hurdles in the transgender population that are discussed within.